The discourse representation of policy makers and stakeholders on language policy matters in Malaysia - Tharmalingam, Selvarajah (2014)
Language issues and controversies in relation to language policies are not uncommon in multiethnic societies, and Malaysia is no exception. With globalization in mind, the Ministry of Education (MOE) implemented a new language policy in 2003 targeting the use of English in teaching and learning Science and Mathematics in English. Known as PPSMI (a Malay acronym), the new policy was rescinded in favour of a politically appropriate policy (MBMMBI), one that ensures the usage of Malay language as a medium of communication in all national schools and secondary schools. However, this decision attracted contestations among people of all walks of life. The policy makers maintained that MBMMBI is the way forward while the proponents of PPSMI stressed that it is a regressive decision. The discourse representation of the policy makers and the stakeholders are collected from three different newspapers: Utusan Malaysia, The Star and The New Straits Times and three online portals: Malaysiakini, Malaysian Insider and Free Malaysia Today. The Critical Discourse Analysis (CDA) method is used to examine the ‘discourse representation’ of the policy makers and the stakeholders in determining the future direction of the MBMMBI policy.